Local People Attitudes towards Community Forestry Practices: A Case Study of Kosti Province-Central Sudan - Amani Abdel Rahim Kobbail (International Journal of Forestry Research)
This paper examines the attitudes of local communities toward community forestry programmes implemented by a project under the CF approach in Kosti area, based on a survey of 100 people living there. The household was the basic unit of data collection; ten villages were selected as study localities. Ten respondents from each village were randomly chosen for the interview. Frequency distribution results showed that almost all the respondents have a particularly favourable perception of the community forestry programmes implemented and they perceive the best type of management for running these forests which is to be owned and managed by them. They participated in different programe activities and willing to further participation in tree planting activities. Women have possessed positive attitudes towards community forestry although they were not fully involved in community forestry Practices. Stepwise multiple linear regression analysis showed a statistical significant relation between some selected variables (Respondents age, educational level, main occupation, respondents indigenous knowledge, family uses of different forestry products, awareness of causes of forest destruction and finally respondents awareness of environmental problems) exerted important influences on the attitudes and participation of respondents. This study suggests that the project and the forest services should continue addressing local development needs, encourage women's participation in community forestry, and work toward dispute settlement of community forest-user groups, if it wants to win the support of local communities for long-term environmental conservation goals.